How Strongly Does German Residential Construction React to Rising Capital Market Interest Rates? - Norbert Hiller; Oliver Lerbs (Wirtschaftsdienst)
Abstract New housing construction in Germany is under heavy pressure. In addition to strongly rising material, labour and energy prices, the costs of financing construction have increased sharply since the start of the year. Due to high inflation in the Eurozone, capital and mortgage rates have increased significantly. In 2021 already, new housing completions went down by four percent year-to-year. This article takes an empirical look at how German housing construction has reacted to past changes in capital market interest rates. We find that without taking appropriate measures, a heavy drop in housing construction is very likely. This central policy aim of the German government would be pushed into the distant future.